Grain boundary segregation in Ni-base alloys: A combined atom probe tomography and first principles study. (December 2021) - Ebner, Anna Sophie; Jakob, Severin; Clemens, Helmut; Pippan, Reinhard; Maier-Kiener, Verena; He, Shuang; Ecker, Werner; Scheiber, Daniel; Razumovskiy, Vsevolod I.
Graphical abstract: Abstract: Grain boundary engineering (GBE) plays an important role in the design of new polycrystalline materials with enhanced mechanical properties. This approach has been shown to be very effective in design of Ni-base alloys, where grain boundary segregation is expected to play a central role in defining their mechanical behavior. In the present work, we apply a powerful combination of advanced experimental and theoretical methods to reveal the grain boundary chemistry of the 725 Ni-base alloy at the atomic level. The methods of investigation comprise atom probe tomography (APT) measurements and density functional theory (DFT) calculations. We also propose a way to cross-validate DFT and APT results in a DFT-based model approach for evaluation of the interfacial excess as a function of the heat treatment history of the material and its chemistry. Both theoretical and experimental methods are applied to a detailed analysis of the GB chemistry of three modifications of the 725 alloy and the results of this investigation are presented and discussed in detail.